2019
DOI: 10.3390/jfmk4030062
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Fat Mass Following Creatine Supplementation and Resistance Training in Adults ≥50 Years of Age: A Meta-Analysis

Abstract: Aging is associated with an increase in fat mass which increases the risk for disease, morbidity and premature mortality. Creatine supplementation in combination with resistance training has been shown to increase lean tissue mass in adults ≥50 years of age; however, the synergetic effects of creatine and resistance training on fat mass in this population are unclear. Creatine metabolism plays an important role in adipose tissue bioenergetics and energy expenditure. Thus, the combination of creatine supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 42 publications
(55 reference statements)
3
15
0
Order By: Relevance
“…A recent systematic review and meta-analysis of 19 studies involving older adults (n = 609 participants; ≥50 years of age) showed that the combination of CR and RT resulted in a greater reduction in fat mass (0.5 kg, p = 0.13) and body fat% (0.55%, p = 0.04) compared to PLA and RT [75]. Mechanistically, creatine appears to also influence adipose tissue biology.…”
Section: Potential Of Creatine Supplementation For Sarcopenic Obesitymentioning
confidence: 99%
“…A recent systematic review and meta-analysis of 19 studies involving older adults (n = 609 participants; ≥50 years of age) showed that the combination of CR and RT resulted in a greater reduction in fat mass (0.5 kg, p = 0.13) and body fat% (0.55%, p = 0.04) compared to PLA and RT [75]. Mechanistically, creatine appears to also influence adipose tissue biology.…”
Section: Potential Of Creatine Supplementation For Sarcopenic Obesitymentioning
confidence: 99%
“…Creatine supplementation while following an energy-restricted diet may be an effective strategy to maintain muscle mass, promote fat loss, and help manage adult-onset obesity. In support of this contention, Forbes and colleagues [ 176 ] recently conducted a meta-analysis on the effects of creatine on body composition and found that creatine supplementation may not only help maintain muscle mass but also promote fat mass loss. This strategy could be helpful in preventing or managing adult-onset obesity.…”
Section: Role Of Creatine In Aging Populationsmentioning
confidence: 99%
“…Creatine may influence muscle biology by stimulating cellular hydration status, calcium kinetics, glycogen content, muscle protein kinetics, satellite cells, growth factors, inflammation and oxidative stress, which have been implicated in enhancing muscle health (for reviews see [ 216 , 220 , 225 , 228 ]. Creatine also plays a role in thermogenesis and whole body energy expenditure [ 229 , 230 , 231 ], which is associated with adiposity.…”
Section: Potential Supplements For Type 2 Diabetesmentioning
confidence: 99%
“…In healthy older adults, supplementing with creatine during a resistance training program increased muscle mass (+1.37 kg) and decreased fat mass (0.5 kg) more than placebo and resistance training [ 218 , 229 ]. Individuals with T2D often have low muscle quantity and increased adiposity; therefore it appears that creatine combined with exercise may be a viable strategy to enhance body composition.…”
Section: Potential Supplements For Type 2 Diabetesmentioning
confidence: 99%